A Synopsis of the Development of a Framework of Reference for English Language Education in Thailand (FRELE-TH) - Lekpetch, Kunchalee; Foley, Joseph (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The purpose of this article is to address the need for a Framework of Reference for English Language Education in Thailand (FRELE-TH 2017) based on the Common Europe Framework of Reference for Languages (CEFR, 2001 2018) which was first introduced and practiced among the European countries. CEFR framework has been adopted into language education systems of the majority of Asian countries as well as other parts of the world. As English is the working language of the ASEAN Economic Community people can cross borders to fulfil their social, economic and educational needs. However many Thais do not have the proficiency in English to compete in terms of English, thus hindering their mobility within the ASEAN context. By looking at the basic principles that would benefit the English language teaching and learning in Thailand using FRELE-TH and understanding the difficulties when adopting and modifying CEFR ‘CAN Do’ approach might be a more realistic solution to improving the standard of English in the Thai education system.